Elaboration of Information Technology Adoption and Employee Productivity in Moderation of Business Sustainability Determinants - Tri Nur Rohmah; Iwan Budiherwanto (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The purpose of this study is to investigate the direct effects of organizational commitment and environmental factors on business sustainability, while also testing the role of information technology adoption and employee productivity in moderating these effects. Method: quantitative approach with primary data collected by sampling through the Lemeshow alpha 5% approach obtained by 384 respondents consisting of leaders and employees of 1, 2, 3 star hotels in Central Java Province. Influence analysis using the least squares regression method, and indirect influence test using the moderated regression analysis technique. Especially for the indirect influence test is built based on the results and recommendations of previous studies using bibliography and systematic literature review methods. Results: organizational commitment and environmental factors each provide a significant positive influence in improving the sustainability of the hotel business. This influence is stronger when the company adopts information technology and is supported by high employee work productivity. These findings present a novelty in the hotel sector to maintain business sustainability, it is time for management to elaborate between information technology and increasing employee productivity.